Quantitative Damage and Fracture Mode of Sandstone under Uniaxial Load Based on Acoustic Emission - Ying Xu; Qiangqiang Zheng; Xin Gao; Rongzhou Yang; Xian Ni; Qianqian Wang (Advances in Civil Engineering)
The damage degree and fracture mechanism of the rock are important to the bearing performance of the rock mass and the stability of the overlying structure. Most of the existing damage models for characterizing rock damage exclude the range of postpeak stress or do not consider the compaction and closure stage of the fracture, and the description of the quantitative damage of sandstone is not accurate enough. In addition, the description of the rock fracture mechanism under load is not exact enough. Aiming at the problem of quantitative damage and fracture mechanism of the loaded rock, this paper adopts acoustic emission (AE) to monitor the loading process of sandstone under uniaxial loading. In accordance with the characteristics of the AE signal, the loading stage of sandstone under uniaxial load is divided into three stages: initial hit stage, hit stability stage, and hit instability stage. By modifying the traditional damage model and combining the AE signals of the sandstone under the load, a modified damage mechanics model is obtained, which can fully express the entire loading stage. Furthermore, through the analysis of AE signals, the fracture mechanism of sandstone under uniaxial load is studied. The results show that the modified damage model can quantitatively describe the damage at different loading stages which include two areas including the fracture compaction closure stage and the postpeak stress stage. The failure and instability of sandstone under uniaxial load is mainly shear failure. The research results can provide a reference for the nondestructive testing of sandstone and engineering reliability in geotechnical engineering.